Analisis Kreativitas Peserta Didik pada Materi Bangun Ruang Model Pembelajaran PJBL di SDN Kauman 1 Malang - NURAINI, AMANDA DEFI; Restian, Arina; Ismanto, Puguh Hadi (J-SES : Journal of Science, Education and Studies, 2025)
This study aims to implementation of the Project-Based Learning (PjBL) model in enhancing students' creativity in understanding the material of spatial geometry in class 6C at SDN Kauman 1 Malang. PjBL was chosen as it is believed to effectively foster creativity, collaboration, and problem-solving skills. This research adopts a qualitative approach, which includes direct observation, in-depth interviews, and documentation of students' work. The findings indicate that the implementation of PjBL effectively develops students' creativity, particularly in terms of imagination, shape analysis, and collaboration skills. Overall, this model has a positive impact on the mathematics learning process in class 6C.